Scientific Literacy Profile of Prospective Science Teacher Students - Putri Sarini; Wahono Widodo; Suyatno Sutoyo; I Nyoman Suardana (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This research aims to describe and analyze the scientific literacy achievements of prospective science teacher students. Scientific literacy is one of the skills that prospective science teacher students must master to promote scientific literacy at the primary and secondary education levels. Method: This research is a quantitative descriptive research. Data was collected using a purposive sampling technique so that a sample of 65 students from the Bachelor of Science Education Study Program at Ganesha University of Education was obtained. The research instrument used was the Test of Scientific Literacy Skills (TOSLS) which consisted of 28 multiple-choice questions. This research is a preliminary study of research and development (R&D) of innovative science learning models to increase students' scientific literacy. Results: The results of the research show that the literacy achievement of prospective science teacher students is very low with the scientific literacy achievement in the aspect of identifying and assessing inquiry methods that contribute to scientific knowledge at very low and the aspect of compiling, analyzing, and understanding quantitative data and scientific information of very low. Novelty: This research provides an overview of the scientific literacy achievements of prospective science teacher students which can be used as a basis for developing innovative science learning models to increase the scientific literacy of prospective science teacher students.